The role of anxiety and related states in pediatric postsurgical pain - Cheryl H. T. Chow; Louis A. Schmidt; D. Norman Buckley (Taylor & Francis Group, 2020)
Background: Nearly 20% of children and adolescents have pain with disability 1 year after surgery, and they experience poor sleep, school absence, and decreased activities. Negative clinical, psychological, and developmental effects include greater pain medication use, longer recovery, and fear of future medical care. Research has found psychological and family influences (i.e., child and parental anxiety) on pediatric chronic postsurgical pain (CPSP), but a better understanding of the role of perioperative anxiety and its related states in predicting pediatric postsurgical pain is needed. The poor understanding of the causes of child CPSP can lead to misdiagnosis and inadequate treatment, with significant short- and long-term effects. Objectives: The aim of this review was to summarize the literature on children's perioperative anxiety and parental anxiety in relation to acute postsurgical pain, CPSP, and pain trajectories. We also examined other related psychological factors (i.e., anxiety sensitivity, catastrophizing, pain anxiety, and fear of pain) in relation to pediatric acute and chronic postsurgical pain. Lastly, we discuss the interventions that may be effective in reducing children's and parents' preoperative anxiety. Conclusions: Our findings may improve the understanding of the causes of CPSP and highlight the gaps in research and need for further study.